Analysis of Volatile Compounds from Different Parts of Houttuynia cordata Thunb - Lin, Chen-Hsiang; Chao, Louis Kuoping; Lin, Li-Yun; Wu, Chin-Sheng; Chu, Lee-Ping; Huang, Chien-Hsueh; Chen, Hsin-Chun (Molecules (Basel, Switzerland), 2022)
Houttuynia cordata Thunb. is a medicinal and edible plant that has been commonly used in traditional Chinese medicine since ancient times. This study used headspace solid-phase microextraction (HS-SPME) and direct injection, combined with gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS), to identify the volatile compounds in H. cordata. Extraction from different parts of the plant using different extraction techniques for the identification of volatile compounds were determined. A total of 93 volatile components were analyzed in the leaves, stems, rhizomes, and whole plant samples of H. cordata. The leaves contained more (Z)-3-hexenal, β-myrcene, (Z)-β-ocimene, and (4E,6E)-allo-ocimene; the stems contained more geranyl acetate and nerolidol; and rhizomes contained more α-pinene, β-pinene, limonene, 2-undecanone, and decanoyl acetaldehyde. Among them, the essential oil extracted by HS-SPME could produce more monoterpenes, while direct injection could obtain higher contents of aliphatic ketones, terpene esters, sesquiterpenes, and was more conducive to the extraction of 2-undecanone and decanoyl acetaldehyde.